Rate of Social Isolation by Geographic Location Among Older Adults: AAA LongROAD Study - Laura Lynch; Thelma J. Mielenz; Guohua Li; Guohua Li; David W. Eby; Lisa J. Molnar; Marian E. Betz; Carolyn DiGuiseppi; Linda L. Hill; Vanya Jones; David Strogatz (Frontiers Media S.A., 2021)
Introduction: Social isolation is a modifiable risk factor for negative health outcomes among older adults. This work assessed the relationship between geography (i.e., urban vs. non-urban residence) and social isolation in a cohort of older drivers.Methods: The AAA LongROAD cohort with 2,989 older adult drivers from across the country were included. Social isolation was measured at baseline and at two subsequent annual follow-ups using PROMIS v2.0 Social Isolation 4a. The effect of geographic location with social isolation was assessed through with multivariable regression using a generalized estimating equation model.Results: The rate of social isolation in urban areas was 21% lower (adjusted RR 0.79, 95% CI 0.46, 1.36) compared to non-urban areas after adjusting for covariates, though not significant.Discussion: Social isolation is a predictor of poor health outcomes and geographic considerations have been lacking in the literature. The panel data in this analysis provides more evidence for causality though the under-representation of non-urban areas potentially reduces the power for the results.Conclusions: It is important to understand the needs and risk of social isolation in various geographic settings to ensure resources and interventions are appropriately modified for a greater public health impact.